Synthesis and characterization of supercapacitive behavior of electrodeposited PANI/Co3O4 layered composite electrode. Issue 1 (2nd January 2016) - Padwal, P.M.; Kadam, S.L.; Mane, S.M.; Kulkarni, S.B.
Abstract : Abstract : Polyaniline (PANI), cobalt oxide (Co3 O4 ) and PANI/Co3 O4 layered thin films are successfully synthesized on stainless steel substrate using electrodeposition technique. The electrochemical oxidation (anodic) method is employed for oxidation of layered composite. The structural and morphological studies of these films are investigated using X-ray diffraction and scanning electron microscope. The electrochemical supercapacitive behavior of the films is studied using cyclic voltammetry and galvanostatic charge–discharge measurements in 0.5M Na2 SO4 electrolyte bath. The layered composite PANI/Co3 O4 electrode shows almost 50% increase in specific capacitance and remarkable enhancement in specific energy and specific power in comparison with the parent Co3 O4 electrode. For layered composite electrode after 500 cycles of charge–discharge, it is observed that specific capacitance retains ∼ 100% compared to the first cycle. The electrochemical impedance spectroscopy is also studied. The simulated values of resistance and capacitance are calculated along with equivalent circuit. Hence, the layered composite PANI/Co3 O4 electrode may have great potential application for electrochemical supercapacitors.